You. The complete first season [videorecording (DVD)] - Berlanti, Greg; Gamble, Sera (Warner Bros. Home Entertainment, 2020)
A 21st-century romantic thriller centered around a relationship that gets taken too far, When a brilliant bookstore manager crosses paths with an aspiring writer, his answer becomes clear: anything. As he uses the internet and social media to gather the most intimate of details to get close to her, a charming and awkward crush quickly becomes obsession when he quietly and strategically begins to remove every obstacle, and person, between them.